2020
DOI: 10.1177/2040622320961597
|View full text |Cite
|
Sign up to set email alerts
|

The effects of telemedicine on the quality of life of patients with lung cancer: a systematic review and meta-analysis

Abstract: Background and aims: Lung cancer patients suffer from deterioration in their physical and psychological function, which exerts a negative influence on their quality of life (QOL). Telemedicine has been proven to be an effective intervention for patients with several chronic diseases. The aim of this systematic review and meta-analysis was to investigate the efficacy of telemedicine in improving QOL in lung cancer patients. Methods: PubMed, Cochrane Library, EMBASE, Web of Science and Scopus databases were sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 38 publications
3
23
0
Order By: Relevance
“…The study’s findings revealed that patients in the telemedicine group had a significantly higher quality of life and less anxiety and depression than patients receiving regular care. 23 Telemedicine is one type of telehealth managed by doctors. This meta-analysis demonstrated the consistency of results from telehealth use, including telenursing, in improving quality of life and other positive effects.…”
Section: Discussionmentioning
confidence: 99%
“…The study’s findings revealed that patients in the telemedicine group had a significantly higher quality of life and less anxiety and depression than patients receiving regular care. 23 Telemedicine is one type of telehealth managed by doctors. This meta-analysis demonstrated the consistency of results from telehealth use, including telenursing, in improving quality of life and other positive effects.…”
Section: Discussionmentioning
confidence: 99%
“…In order to ensure high-quality healthcare in the future—especially in rural areas—various innovations have been developed in primary and secondary care that have integrated TM applications as a central component [ 24 ]. Recently, these TM applications have been the subject of many studies and reviews to investigate or prove their effectiveness [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. While morbidity and clinical indicators have been defined as primary outcome indicators for TM applications in selected disease groups, such as chronic heart failure, QoL has been defined as a primary outcome indicator from patients’ perspective.…”
Section: Relevancementioning
confidence: 99%
“…While morbidity and clinical indicators have been defined as primary outcome indicators for TM applications in selected disease groups, such as chronic heart failure, QoL has been defined as a primary outcome indicator from patients’ perspective. Reviews [ 12 , 25 ] have shown that it has not yet been possible to document the effect of telemonitoring on QoL, and the findings are inconsistent across specific clinical patient groups and different TM applications [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. However, the effects of telemonitoring on the daily life of patients, as well as their QoL, well-being, and the subjective experience of control, appear to be considerable: they go beyond the intended health effects and also affect psychosocial and ethical aspects [ 13 , 26 ].…”
Section: Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…(25) Similarly, other RCTs found that cognitive behavior therapy delivered through telephone for 8 to 12 weeks significantly decreased patient reported symptoms (treatment effect = 0.36, 95% CI: 0.01-0.70; p = 0.043)(26) and decreased depression scores significantly at 6 months follow up (β =-.41,p=.018). (27)A meta-analysis showed that telemedicine was significantly effective to increase QoL among lung cancer patients [standard mean difference= 0.96, 95%, CI: 0.29-1.63] (28). Another study used a 12-Item Health Survey scale among veterans who were provided home based video physiotherapy that showed significant improvement in QoL after intervention (p = 0.02, r = 0.42).…”
mentioning
confidence: 99%